The Degree of Readiness to Total Distance Learning in the Face of COVID-19 - Teachers’ View (Case of Azerbaijan, Georgia, Iraq, Nigeria, UK and Ukraine) - Doghonadze, Natela; Aliyev, Aydin; Halawachy, Huda; Knodel, Ludmila; Adedoyin, Adebayo Samuel (Journal of Education in Black Sea Region, 2020)
By distance learning we understand an educational situation in which a teacher and his/her students are not placed in one physical environment. Distance learning was first applied in the 19th century and has undergone a long way of technological improvement. It has become indispensable in the time of global pandemic. It is characterized by both advantages and challenges, and, correspondingly, in normal situations is used by adults for additional education or at any level /age in combination with traditional face-to-face education. The goal of this paper is to assess how ready we turned out to be to involuntary, caused by extreme situation of coronavirus, switching over to distance learning. The article presents results obtained from six countries – Azerbaijan, Georgia, Iraq, Nigeria, UK, and Ukraine - as well as some views of educators from several other countries. Although the samples were not representative by number of the research populations, they tried to take into consideration the strata involved (school/university teachers, younger than 30, 31-50, older than 50), in order to be trustworthy. The conclusion made is that the trend is that we (at least, in many countries, or many of us) are still rather far from ready to carry out so often declared and advertised distance learning with optimal efficiency and much work is needed to be able to switch to high-quality distance education.